2018
DOI: 10.1176/appi.ps.201700145
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Serious Emotional Disturbance Among U.S. Children: A Meta-Analysis

Abstract: These estimates of SED are sufficiently precise to meaningfully guide clinical decision making, mental health policy, and consideration of child psychiatry workforce needs in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
30
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 52 publications
(76 reference statements)
0
30
0
1
Order By: Relevance
“…It is estimated that .1 in 10 youth in the United States has a serious psychiatric disorder. 1 Many of these children, however, never receive treatment. 2 For those in crisis (eg, suicide ideation, aggression, and psychosis) or without accessible connections to the mental health care system, the emergency department (ED) has become the national safety net because this setting is obligated to treat all patients regardless of day or time, reason for referral, or availability of financial payment.…”
mentioning
confidence: 99%
“…It is estimated that .1 in 10 youth in the United States has a serious psychiatric disorder. 1 Many of these children, however, never receive treatment. 2 For those in crisis (eg, suicide ideation, aggression, and psychosis) or without accessible connections to the mental health care system, the emergency department (ED) has become the national safety net because this setting is obligated to treat all patients regardless of day or time, reason for referral, or availability of financial payment.…”
mentioning
confidence: 99%
“…The reason for which could be the obvious depression, anxiety, stress observed by the both at-risk populations due to the challenges of transition from one age group to the next one (Collins & Munoz-Solomando, 2018;Nebhinani& Jain, 2019). The major challenges for adolescents constitute of bodily changes (i.e., development of secondary sex characteristics) (Kar, Choudhury, & Singh, 2015;McAteer et al, 2017;Pringle et al, 2016), peer group pressure Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: 25 July 2020 doi:10.20944/preprints202007.0620.v1 (Moldes, Biton, Gonzaga, & Moneva, 2019;Singh, 2017;Tripathy, 2018), behavioral and emotional disturbances (Borba & Marin, 2018;Osman, Khalaf, Omar, & Ismail, 2019;Williams, Scott, & Aarons, 2018). The young adults, on the other hand, face challenges of transition from adolescent to adulthood (Fegert, Hauth, Banaschewski, & Freyberger, 2016;Switek & Easterlin, 2018), financial pressure (Dewilde, Hubers, & Coulter, 2018;Lennartz, Arundel, & Ronald, 2016;Stein et al, 2013), conflict at the stage of isolation vs. intimacy (Mackinnon, De Pasquale,, & Pratt, 2016), personal development (Bonnie et al, 2015), and change in outlook towards life (Switek & Easterlin, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of mental disorders in childhood has been increasing, ranging from around 13.4%, in community surveys around the world [ 4 ], up to 49% in clinical populations [ 5 ]. The US prevalence of youths with serious emotional disturbance with global impairment is about 6.36% [ 6 ]. In Brazil, studies have reported a prevalence of 30% of common mental disorders in adolescents [ 7 ] with 50% of adult mental disorders beginning before the age of 18 years [ 8 ].…”
Section: Introductionmentioning
confidence: 99%